In search of a level playing field : the implementation of the Basle Capital Accord in Japan and the United States - Scott, Hal S.; Iwahara, Shinsaku; Group of Thirty (Washington, D.C. : Group of Thirty, 1994)
This study examines the implementation of the 1988 Basle Capital Accord in Japan and the United States.
Includes bibliographical references.
osc 03/10/2017
Loans
Keywords: Banks and banking, International; Liquidity (Economics); Capital - Financial economics; Competition, Unfair